Investigating the moral compensatory effect of unethical pro-organizational behavior on ethical voice - Xia, Fubin; Lu, Ping; Wang, Lifang; Bao, Jiangdong (Frontiers in Psychology, 2023)
Unethical pro-organizational behavior (UPB) can hinder the sustainable development of the organization. The existing literature on UPB rarely examines whether and how employees remedy such ethical misconduct after they have committed it. Based on moral compensation theory and social exchange theory, this study explores the self-moral compensation process of employees who engage in UPB. Specifically, we adopt a moderated mediating model to examine how and when UPB facilitates ethical voice. Data from 415 full-time employees in Chinese companies at the three-stage questionnaire revealed that UPB has a significant positive effect on ethical voice, and moral ownership plays a mediating role between UPB and ethical voice. Furthermore, the results support the moderating role of benevolent leadership on the positive direct effect of UPB on ethical voice, and the positive indirect effect of UPB on ethical voice via moral ownership. When benevolent leadership is high, the direct effect of UPB on ethical voice and the indirect mediating effect of moral ownership are both significantly positive, while neither are not significant when benevolent leadership is weak. These findings showing the ethical compensation effect of UBP on ethical voice provide a novel and comprehensive understanding of the consequences of UPB, and have significant value for ethical practices in managing employee (mis)behavior.